The Role of Internal Control Systems in Enhancing Local Financial Report Accountability - Yaya Sonjaya; Sri Iswati; Muslim Muslim (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
This study analyzes the influence of budget planning and budget participation on the accountability of financial reports in Papua Province's Regional Apparatus Organizations (OPD) and examines the moderating role of the internal control system. A quantitative causality approach was applied, with a sample of 105 State Civil Apparatus (ASN) from 35 OPDs selected through a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with moderation testing via the bootstrap method. The results indicate that budget planning and participation significantly enhance financial report accountability. Additionally, the internal control system moderates these relationships, reinforcing accountability. This study provides valuable insights into factors influencing financial report accountability in Papua’s OPDs and highlights the importance of internal control systems in strengthening budget-related accountability measures.